Participatory mapping as a tool for social change: a tale of community development efforts in Northeast Kansas and Western Guatemala - Jeje, Emmanuel Akinlolu (My University, 2025)
Compared to urban areas, small and rural communities generally face challenges such as poverty lower educational, lack of infrastructure and services and limited connectivity, (Hunsaker & Kantayya, 2010; Organization for Economic Co-operation and Development, 2016). Post and Ruelle (2021) note that challenges of rural areas highlight the need for deeper engagement between universities and communities through community-engaged scholarship (CES). Cinderby (2010) describe participatory mapping as crucial for fostering collaboration and engagement among diverse community members and stakeholders. However, it is difficult to achieve collaborative action in small and rural areas due to prevailing challenges in these areas (White & Boyle, 2021). If small and rural communities continue to underutilize collaborative actions that CES and participatory mapping potentially bring, these rural areas are more likely to miss out on the social change and transformative benefits of collaborative relationships and such areas will fall behind in terms of community development. The purpose of this qualitative multiple case study was to explore how local dynamics, individual reflections and collective experience shape engagement in social change through participatory mapping processes in small and rural communities. To address this purpose, this study examined the experiences of 13 local residents in two small and rural communities—Ogden, Kansas in the United States and Panajachel, Sololá in Guatemala. The research gap addressed is a general paucity of literature exploring how to use participatory mapping in rural CES projects (McCall & Dunn, 2011). Most studies on CES are conducted in non-rural contexts where resources, infrastructure, and digital literacy are higher (Sutin & Bethea, 2015). There is a general lack of studies exploring how participatory mapping and CES can be integrated to contribute to positive social change and community development in small and rural communities. The qualitative research approach was guided by an interpretivist perspective, and I conducted this exploratory multiple case inquiry through the lenses of the social change, innovation, and technology and social change leadership framework. The study participants were purposively selected from local citizens, business proprietors, civic leaders and community organizations representatives who had previously participated in the participatory mapping process facilitated in Ogden and Panajachel preceding this study. I conducted semi-structured interviews with four participants in Ogden and seven participants in Panajachel. Two rounds of one focus group discussion were conducted in Ogden, Kansas and it consisted of six participants and two rounds of focus groups comprising seven participants were conducted in Panajachel. The qualitative data was analyzed using thematic analysis, chiefly the inductive approach. The major findings of the study illustrated that in the small and rural communities of Ogden, Kansas and Panajachel, Guatemala, there are historically low levels of collaboration among community members and leadership challenges (lack of clear purpose, vision and passion, lack of knowledge and skills, lack of effective communication) and lack of resources pose as challenges to collaboration and any efforts designed to bring social change. The findings demonstrate understanding the purpose of collaboration, effective communication, motivated community members, community advocates, and inclusivity are critical pre-conditions that should prevail for successful collaboration and participatory mapping process. The findings showed that the participatory mapping processes contributed to capacity building at both community level (community awareness and knowledge acquisition) and individual levels (empowerment, decision-making, knowledge and experience acquisition). Based on the findings the recommendations provided include ((a) institutionalize participatory mapping in community mapping process, (b) advocacy and mobilization, (c) develop community structures to act as center of collaboration and engagement, (d) intentionally involve people that are disengaged in community development.
Keywords: Collaboration; Collective power; Community engagement; Participatory mapping